Tinnitus: Mechanisms Induced from Human Functional Neuroimaging Studies - Maudoux, Audrey; Lefebvre, Philippe (Seminars in Hearing, 2014)
The past 15 years has provided an unprecedented collection of discoveries that bear upon our scientific understanding of the pathophysiology of tinnitus. Highlighted among these discoveries is the fact that changes of brain activity accompany tinnitus. All tinnitus theories refer to common concepts. First, peripheral lesions in the cochlea or the auditory nerve produce dysfunctional input to central auditory structures and induce changes in the auditory system. Associated to plastic changes in central auditory structures, neuroimaging studies show signs of the implication of extra-auditory regions in tinnitus pathophysiology. Collectively, these observations have led to important new insights into the understanding of tinnitus. Here, we review the advances made in this field of research using human functional neuroimaging methods.
Keywords: Neuroimaging methods; tinnitus; functional magnetic resonance imaging; positron emission tomography; electroencephalography; magnetoencephalography; connectivity; resting state